Trimethylaluminium‐Mediated Reaction of Primary Carboxamides with Amines and Indoles: A Convenient Synthesis of Amidines and Indole‐3‐acylimines. Issue 26 (30th July 2014) - Velavan, A.; Sumathi, S.; Balasubramanian, K. K.
Abstract: A simple, convenient and general method, exhibiting good functional group tolerance, is described for the synthesis of N ‐ and N, N ‐disubstituted amidines by the reaction of primary carboxamides with amines mediated by trimethylaluminium (AlMe3 ). Subsequent reaction of the indole systems with primary carboxamides in the presence of AlMe3 gives exclusively the C‐3 substituted imine product. Abstract : Primary carboxamides are found to be suitable substrates for trimethylaluminium‐mediated one‐step synthesis of N ‐ and N, N ‐disubstituted amidines. By using this methodology, the synthesis of a diverse class of amidines from primary carboxamides and amines is described. The one‐step synthesis of indole C3 acylimines was also demonstrated from primary carboxamides and free NH indole systems mediated by AlMe3 .